When Saying Sorry May Not Help: The Impact of Apologies on Social Rejections - Freedman, Gili; Burgoon, Erin M.; Ferrell, Jason D.; Pennebaker, James W.; Beer, Jennifer S. (Frontiers in Psychology, 2017)
If you have to socially reject someone, will it help to apologize? Social rejection is a painful emotional experience for targets, yet research has been silent on recommendations for rejectors. Across three sets of studies, apologies increased hurt feelings and the need to express forgiveness but did not increase feelings of forgiveness. The investigation of hurt feelings arising from a social rejection is challenging because previous research has shown that participants are reluctant to admit they felt hurt by the rejection. The present research addressed the self-report issue in two ways. First, participants rated how much social rejections would hurt someone’s feelings as a function of whether an apology was included across various social rejection scenarios (Studies 1a-e). Second, aggressive behavior was measured in response to face-to-face social rejections that were manipulated to include or exclude apologies (Studies 2a-c). More specifically, Studies 1a-e (N = 1096) found that although individuals sometimes use apologies in social rejections, social rejections with apologies are associated with higher levels of explicit hurt feelings. Studies 2a-c (N = 355) manipulated the presence of an apology in face-to-face social rejections and found that social rejections with apologies cause more aggressive behavior. As in previous research, participants are reluctant to admit to feeling hurt. Finally, Study 3 (N = 426) found that in response to social rejections with apologies, individuals feel more compelled to express forgiveness despite not actually feeling more forgiveness. Implications for the role of language in social rejections are discussed.